FINANCING COLLATERAL ASSESSMENT PROCEDURE USING MURABAHAH AGREEMENT FOR PNS (CIVIL SERVANTS) AT PT BANK ACEH SYARIAH LHOKSEUMAWE BRANCH - Hamdiah; Likdanawati; Sutriani (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2024)
Collateral is an asset or valuable item entrusted by a customer to the bank as collateral. This collateral can transfer ownership rights to the bank if the borrower does not fulfill his obligation to return the funds according to the agreement. Customers and loans with collateral usually pay lower interest than loans without collateral because the bank has a lower risk of loss. Procedure for assessing financing collateral using a murabahah contract for civil servants (civil servants) at PT. Bank Aceh Syariah Lhokseumawe Branch has several stages, namely collecting information, identifying assets, assessing market value, document verification, murabahah contract, securing and registering collateral. Collateral appraisal is very important because it can have an impact on loan or financing approval, determining the selling price or asset value in the case of buying and selling, as well as in making business and investment decisions. Therefore, the collateral assessment process must be carried out professionally and objectively to produce accurate and accountable conclusions. Obstacles in the procedure for assessing financing collateral using a murabahah contract for civil servants (civil servants) at PT. Bank Aceh Syariah Lhokseumawe Branch, namely limited documents and information, limited assets pledged as collateral, internal policies of the bank or financing institution, market value that is difficult to determine, limited valuation methods. Efforts that can be made in the financing collateral assessment procedure using a murabahah contract for civil servants (civil servants) at PT. Bank Aceh Syariah Lhokseumawe Branch, namely by improving communication and coordination, customer education, collaboration with related agencies, the use of independent appraisers, improving Bank Aceh Syariah's internal policies, and training and development of appraisers.